2019
DOI: 10.3174/ajnr.a6073
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose and Image Quality in Pediatric Neck CT

Abstract: BACKGROUND AND PURPOSE: Optimization of pediatric neck CT protocols is of critical importance in order to maintain good diagnostic image quality while reducing the radiation burden. Our aim was to evaluate the image quality of pediatric neck CT studies before and after the implementation of a low radiation dose protocol. MATERIALS AND METHODS: We retrospectively reviewed 179 pediatric neck CT studies, 75 before and 104 after the implementation of low-dose protocols, performed in children 0-16 years of age. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
(15 reference statements)
0
0
1
Order By: Relevance
“…an ED reduction of 68.58% and 38.03%, respectively, relative to that achieved with the standard 120-kVp protocol. The dose reductions obtained in the present study were smaller than previously reported values [16].…”
Section: Plos Onecontrasting
confidence: 90%
“…an ED reduction of 68.58% and 38.03%, respectively, relative to that achieved with the standard 120-kVp protocol. The dose reductions obtained in the present study were smaller than previously reported values [16].…”
Section: Plos Onecontrasting
confidence: 90%